Effects of taurine supplementation and swimming, associated or not, on obesity and glucose homeostasis in mice - 10.4025/actascihealthsci.v34ispec.10433 - Iris Cheng; Maria Lúcia Bonfleur; Leonardo Eduardo Ferreira; Rosane Aparecida Ribeiro; Sandra Lucinei Balbo (Universidade Estadual de Maringá, 2012)
Studies show that physical exercise (PE) is associated with a reduced fat accumulation and increased insulin sensitivity, and taurine (TAU) improves glucose homeostasis in lean rodents. The aim  in this work was evaluate the effects of supplementing TAU and practice of PE, associated or not, on obesity and glucose homeostasis on obese MSG-mice. Neonate male Swiss mice received injections of monosodium glutamate (MSG group) or saline (CON group). From the 30th to the 90th day of life, one group of animals received TAU in drinking water (MSG TAU group), another was subjected to PE (MSG PE group) and a third group underwent both procedures (MSG PE TAU group). Mice treated with MSG become obese, hypertriglyceridemic, glucose intolerant and insulin resistant. The supplementation with TAU and the PE, isolated or associated, reduced the triglycerides (38%), glucose intolerance (around 30%) and KITT (79%) in MSG-obese animals, but did not influence the accumulation of fat. Interestingly, the combination of both strategies significantly reduced the insulin resistance, compared to animals subjected to isolated strategies. In conclusion, the supplementation with TAU and PE, isolated or associated, did not influence the accumulation of fat in MSG-obese mice, however, reduce the triglycerides and insulin resistance.